Experimental and theoretical study on infinite dilution activity coefficients of various solutes in ionic liquid 1-propyl-2, 3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide. (January 2020) - He, Zhuang-Zhuang; Li, Rui-Qi; Sun, Ai-Lin; Mu, Zhao; Xiao, Yan-Li; Chang, Hui-Wen; Jiao, Yu-Hai; Ge, Ming-Lan
Graphical abstract: Highlights: Measurements of activity coefficients at infinite dilution using GLC. The (gas–liquid) partition coefficients were calculated. The excess thermodynamic functions, entropies, and Gibbs energies were calculated. The solubility parameter of the IL [PMMIM][NTf2 ] was determined. Selectivity and capacity for hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ). Abstract: The infinite dilution activity coefficients ( γ i ∞ ) and gas–liquid partition coefficients ( K L ) of solutes in the ionic liquids (ILs) are important parameters of thermodynamic properties. They can evaluate the separation selectivity ( S ij ∞ ) of ILs and screen out suitable extractants for difficult separation systems. The retention times of solutes in IL 1-propyl-2, 3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide [PMMIM][NTf2 ] were measured by gas chromatography (GC) to calculate the γ i ∞ and the Κ L values of organic solutes (eg. n -alkanes, alkyl benzenes, acetonitrile, tetrahydrofuran, ethyl acetate, etc. ) in [PMMIM][NTf2 ] at 303.15 K-353.15 K. The density of [PMMIM][NTf2 ], as a function of temperature, was measured at p = 101.3 kPa. The values of the partial molar excess enthalpies at infinite dilution ( H - i E, ∞ ) were derived from the T dependence of the l n γ i ∞ . The entropies ( T ref S - i E, ∞ ) and Gibbs free energies ( G - i E, ∞ ) of organic solutes in [PMMIM][NTf2 ] at a reference temperature Τ ref = 298.15 K can be calculated from the γ i ∞ values. The Hildebrand's solubility parameters of the IL [PMMIM][NTf2 ] were obtained from the regular solution theory (RST) combined with Flory "combinatorial" equation. At 323.15 K, the selectivity ( S ij ∞ ) of n -hexane ( i )/benzene ( j ) and cyclohexane ( i )/benzene ( j ) and the capacity ( k j ∞ ) at infinite dilution of benzene have been determined. The results were analyzed by comparing with literature data for alkylimidazolium-based ILs with [NTf2 ] − .